Economic inequalities in decayed, missing, and filled first permanent molars among 8–12 years old Iranian schoolchildren - Maryam Khoramrooz; Seyed Mohammad Mirrezaie; Mohammad Hassan Emamian; Hajar Golbabaei Pasandi; Ali Dadgari; Hassan Hashemi; Akbar Fotouhi (BMC Oral Health, 2023)
Abstract Background First permanent molars (FPM) play an important role in the masticatory function and oral health. This study aimed to assess the economic inequalities of FPM health indices among schoolchildren in the northeast of Iran. Methods A total of 4051 children aged 8–12 years old were included in the analyses of this cross-sectional study in 2015. Economic status was measured using the principal component analysis on home assets. Concentration index (C) was used to measure economic inequality in FPM health indices, and its contributing factors determined by Wagstaff decomposition technique. Results The prevalence of having decayed, missing, and filled FPMs among children was 40.9% (95% CI: 38.8–43.0), 1.2% (95% CI: 0.8–1.6%), and 7.8% (95% CI: 6.7–8.9%), respectively. Missing FPM was generally more concentrated among low-economic children (C=-0.158), whereas, filled FPM was more concentrated on high-economic children (C = 0.223). Economic status, mother education, having a housekeeper mother, and overweight/obesity, contributed to the measured inequality in missing FPM by 98.7%, 97.5%, 64.4%, and 11.2%, respectively. Furthermore, 88.9%, 24.1%, 14.5%, and 13.2% of filled FPM inequality was attributable to children’s economic status, father education, residence in rural areas, and age, respectively. Conclusion There is a significant economic inequality in both missing and filled FPM. This inequality can be attributed to the economic status of individuals. To reduce FPM extraction, it is important to target low-income and rural children and provide them with FPM restoration services. Additionally, it is necessary to provide training to less-educated parents and housekeeper mothers to address the observed inequalities.